Hear him roar: a novel - Wingfield, Andrew, author; Utah State University Press, publisher (Colorado State University. Libraries, 2005)
A cougar attacks a jogger in the suburbs of a western city. Charlie Sayers, facing retirement as a wildlife biologist at a downsized state agency, is drawn into the search for the lion. He gets caught up in the conflict between wildlife habitat and an increasingly developed environment as, teetering between crisis and farce, he tries to piece together the puzzle of his own life.--Provided by publisher.
Part One -- Cougar Country -- The Latest Version -- Haunts -- Val -- Dinner -- The Leap -- The Rescue -- Part Two -- Kyle -- Cougar Alert -- Cory -- Weather -- Paying Attention -- Dinner -- Part Three -- Verity -- Back to the Barn -- Behavioral Enrichment -- Sadie -- Kyle -- Don -- Preparations -- Jambalaya -- Part Four -- On the Bridge -- Sufficient Grounds -- Baiting -- Hear Him Roar -- Part Five -- The Rescue -- Sadie -- Don -- June -- Appetites -- Leaving.
Keywords: Wildlife management -- Fiction; Midlife crisis -- Fiction; Biologists -- Fiction; Puma -- Fiction; California -- Fiction